Analysis of Students' Experience and Satisfaction in Management Use of Academic Information System (SIAKAD) University of Great Nias - Herman Sulvanis Sarumaha; Intan Christine Oktavira Wau; Witer Mawati Halawa; Fidelia Selvianis Harita; Faleria Lotina Waruwu (HARAMAIN: Jurnal Manajemen Bisnis, 2026)
This study aims to analyze students’ experiences and satisfaction in using the Academic Information System (SIAKAD) at the University of Great Nias, focusing on students of the Management Study Program. A qualitative approach with a descriptive qualitative design was employed in this study. Data were collected through in-depth interviews, observation, and documentation involving students who had actively used SIAKAD for at least one semester. Informants were selected using purposive sampling until data saturation was achieved. Data analysis was conducted using an interactive analysis model consisting of data reduction, data display, and conclusion drawing. The findings reveal that students generally have positive experiences in using SIAKAD, particularly in terms of ease of access to academic information, practicality of academic services, and system support for learning activities. Students also reported a satisfactory level of satisfaction, as the system was able to meet their expectations and academic needs. However, several challenges were identified, including system speed and stability during peak usage periods and the need for improvement in interface design to enhance usability. The study concludes that although SIAKAD has provided significant benefits for students, continuous evaluation and system development are necessary to further improve user experience and satisfaction.